PELAKSANAAN TERHADAP PEMENUHAN HAK PERAWAT DI RUMAH SAKIT BINA KASIH PEKANBARU - Purwanti, Windy; Lestari, Rika; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Since Indonesia was established, the Indonesian people have realized that work is a fundamental requirement of citizens. In line with the pace of the Indonesian population, the laborer and the requirment of work will increase. One of the employment opportunities offered to people who have specific knowledge especially nursing and work at the hospital. In considering, so many hospitals in Pekanbaru, the writer took place at Bina Kasih Hospital Pekanbaru, most of caregivers are women. They do not get their rights fully as has been set in Labour Laws and other government regulations that related with labour, epecially the rights that should be obtained for women workers who work at night. The purpose of this research are; First, the implementation and the fulfillment rights of nurses who work at night in the Bina Kasih Pekanbaru. Second, constraints and efforts to implementation and to fulfillment the rights of nurses who work at night in Bina Kasih Hospital Pekanbaru.The type of this research is sociological research. This study was conducted at Bina Kasih Hospital Pekanbaru. The population is the head nurse, nurse permanent and contract then Human Resource Department (HRD). The datas that used is primary data, secondary data and tertiary data. Techniques of collecting data are interviews, questionnaires and literature study.From the research of the problems there are two things that can be concluded. First, the implementation and the accomplishment of the nurses right who working at night in the Bina Kasih Hospital Pekanbaru still not been found, that is; the right to get food and drink, then the right to get security in working. Second, the efforts and constraint that do to fulfillment the rights of nurses, the constraint that got by Bina Kasih Hospital Pekanbaru are there is no balance betwen income and expulsion, then the nurses did not know more what is their rights that should they get when working. To accomplistment the nurses right when the indrustrialist and the laborer made a work relationship from employment aggrement, and made a dealing that contained with all rights and obligations both of them that implement during employment relationship, until the laborer know all their duties that should they do and get when working, in order way the industrialists know their duties and what should they do to give the rights of nurses.Key Word: Fulfillment of Right – Nurse – Bina Kasih Hospital Pekanbaru